Association of Anthropometric Parameters and Severity of SARS-COV-2 Infection among Hospitalized Patients in a Tertiary care Center in Western Maharashtra – an Analytical Cross-Sectional Study - Shewte, Mamta Kishor; Dhok, Rajeshree Sushil; Pachange, Priyanka Narayanrao; Suryawanshi`, Prachi Manohar; Sayed, Naila Nazir (Central Asian Journal of Medical Sciences, 2023)
Background: On March 11, 2020, the World Health Organization (WHO) confirmed COVID-19 as a pandemic. COVID-19 has infected more than 5.5 million people worldwide, resulting in more than 3,47,000 fatalities. Obese individuals may be more susceptible to infection with SARSCoV-2. This study was conducted to assess the association between anthropometric parameters and the severity of SARS-CoV-2 infection. Methodology: This analytical cross-sectional study was undertaken on COVID-19-positive patients admitted to COVID-dedicated wards at a tertiary care center in Pune. The data was collected using a convenient sampling method from 185 COVID-19-positive patients. Result: Among those Positive for SARS-COV-2, 128 (69.19%) patients had mild COVID-19, and 57 (30.81%) patients were having severe COVID-19 disease. 36 patients (28.13%) with mild COVID-19 disease were average weight, 48 patients (37.50%) were overweight, and 42 patients (32.81%) were obese. Three (5.26%) of the 57 patients with severe COVID-19 disease were overweight, and 54 (94.74%) were obese. 19 (10.2%) patients had previously been diagnosed with hypertension, and 22 (11.8%) patients had both hypertension and diabetes. Conclusion: Obesity in patients with COVID-19 was associated with severe diseases, particularly pneumonia. Patients having underlying medical illnesses like hypertension and diabetes were found to be at higher risk of severe COVID-19.